Efficacy of ozonized olive oil in the management of oral lesions and conditions: A clinical trial - Tarun Kumar; Neha Arora; Gagan Puri; Konidena Aravinda; Avani Dixit; Deepa Jatti (Wolters Kluwer Medknow Publications, 2016)
The oral cavity is an open ecosystem that shows a dynamic balance between the entrance of microorganisms (bacterial, viral or fungal), colonization modalities, nutritional balance, and host defenses against their removal. The oral lesions including aphthous ulcerations, herpes labialis, oral candidiasis, oral lichen planus, and angular cheilitis some of the common entities encountered in the clinical practice. A variety of treatment options is available in the literature for all of these lesions and conditions. Topical ozone therapy is a minimally invasive technique that can be used for these conditions without any side effects. Aim and Objectives: To evaluate the efficacy of ozonized olive oil in the treatment of oral lesions and conditions. Materials and Methods: A longitudinal study was carried out on 50 patients (aphthous ulcerations, herpes labialis, oral candidiasis, oral lichen planus, and angular cheilitis). The ozonized olive oil was applied twice daily until the lesion regresses for a maximum of 6 months. Results: All the lesions regress in patients with aphthous ulcerations, herpes labialis, oral candidiasis and angular cheilitis or showed improvement in the signs and symptoms in oral lichen planus patients. No toxicity or side effect was observed in any of the patients. Conclusion: Ozone therapy though requires a gaseous form to be more effective, but topical form can also bring out the positive results without any toxicity or side effect. Hence, it can be considered as a minimally invasive therapy for the oral infective and immunological conditions.